2022
DOI: 10.5194/hess-26-4685-2022
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and benefits of quantifying irrigation through the assimilation of Sentinel-1 backscatter observations into Noah-MP

Abstract: Abstract. In recent years, the amount of water used for agricultural purposes has been rising due to an increase in food demand. However, anthropogenic water usage, such as for irrigation, is still not or poorly parameterized in regional- and larger-scale land surface models (LSMs). By contrast, satellite observations are directly affected by, and hence potentially able to detect, irrigation as they sense the entire integrated soil–vegetation system. By integrating satellite observations and fine-scale modelli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 92 publications
0
34
0
Order By: Relevance
“…An alternative way to assimilate satellite observations is to directly ingest level-1 observations (i.e., brightness temperature or radar backscatter), instead of retrievals Reichle, 2016a, 2016b;Lievens et al, 2017aLievens et al, , 2017bModanesi et al 2022). In particular, Modanesi et al (2022) assimilated 1 km Sentinel-1 backscatter (γ 0 ) observations into the Noah MP LSM, equipped with a sprinkler irrigation scheme into the National Aeronautics and Space Administration (NASA) Land Information System (LIS) framework, for the update of both surface soil moisture and vegetation states. The authors found that DA improves the bias of irrigation simulation although limitations mainly due to irrigation model parameterization still need further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative way to assimilate satellite observations is to directly ingest level-1 observations (i.e., brightness temperature or radar backscatter), instead of retrievals Reichle, 2016a, 2016b;Lievens et al, 2017aLievens et al, , 2017bModanesi et al 2022). In particular, Modanesi et al (2022) assimilated 1 km Sentinel-1 backscatter (γ 0 ) observations into the Noah MP LSM, equipped with a sprinkler irrigation scheme into the National Aeronautics and Space Administration (NASA) Land Information System (LIS) framework, for the update of both surface soil moisture and vegetation states. The authors found that DA improves the bias of irrigation simulation although limitations mainly due to irrigation model parameterization still need further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The WCM calibration was done for each site separately, based on Noah‐MP SSM and LAI simulations and real S1 γVV0 ${\gamma }_{VV}^{0}$ observations, following Modanesi et al. (2021, 2022). The synthetic observations are assimilated after perturbing them with different levels of Gaussian white noise, with standard deviations ranging from 0 to 0.7 dB (see Section 2.4).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that in contrast to the setup of Modanesi et al. (2022), a perturbation bias correction method was applied in this study. This adjustment was proposed by Ryu et al.…”
Section: Methodsmentioning
confidence: 99%
“…The results were consistent with in situ observations over a large and intensely irrigated area, but failed over small agricultural practices, mainly due to spatial mismatch between coarse‐scale MW products (>25 km) and smallholder agricultural plots (<1 km). Despite the promising results from SM2RAIN obtained from these studies, the SM data itself remains a major challenge to this model, in that a higher resolution SM product is needed to detect the irrigation signal (Dari et al., 2020; Foster et al., 2020; Jalilvand et al., 2019; Massari et al., 2021; Modanesi et al., 2022; Zaussinger et al., 2019), while, increasing the spatial resolution corresponds with narrower sensor swath width and less frequent retrievals (Das et al., 2019). Dari et al.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) assimilated SMAP SM observations (using a 1‐D Kalman filter) to constrain the target SM in the Community Land Model (CLM) irrigation module and significantly reduced the irrigation water requirement error over an intensely irrigated area in the U.S. Modanesi et al. (2022) used an Ensemble Kalman Filter (EnKF) to directly assimilate Sentinel 1 backscatter in co‐ and cross‐polarization into the Noah‐MP LSM with an irrigation scheme. They showed that assimilating Sentinel 1 backscatter in the VH polarization (that contains LAI information) can slightly improve irrigation simulations.…”
Section: Introductionmentioning
confidence: 99%